STUDENTS PERCEPTIONS OF ONLINE ENGLISH LEARNING DURING COVID-19 PANDEMIC (CASE STUDY ON COMMUNICATION SCIENCE STUDENTS OF UNSERA, CLASS OF 2021) - Selnistia Hidayani; Rina Fitriana (Jurnal Scientia, 2023)
This study aims to find out Serang Raya University students' perceptions of online English learning done during Covid-19 pandemic. Data collection techniques in this study sre observation and in-depth interviews conducted with 9 informants. The research informants came from representatives of the 2021 Communication Department students. Based on the results of observations and interviews, researchers can conclude that students' perceptions of online English learning are influenced by several factors, namely the learning environment, learning culture and the students' personal self.